Human milk oligosaccharides and non-digestible carbohydrates reduce pathogen adhesion to intestinal epithelial cells by decoy effects or by attenuating bacterial virulence. (January 2022) - Kong, Chunli; de Jong, Anne; de Haan, Bart J.; Kok, Jan; de Vos, Paul
Graphical abstract: Highlights: Inulins and low DM pectin inhibit pathogen adhesion by serving as decoy receptors. Preexposure to 3-FL and DM69 pectin increase adhesion of some E. coli strains. Prevention of adhesion by inulin is strongest with pathogens from logarithmic phase. Enhanced yedE, yohJ, yecH, yqjI may be responsible for enhanced epithelial adhesion. Despite enhanced adhesion, DM69 pectin attenuate bacterial virulence genes. Abstract: This work investigated the effects of different chemical structures of human milk oligosaccharides (hMOs) and non-digestible carbohydrates (NDCs) on pathogen adhesion by serving as decoy receptors. Pre-exposure of pathogens to inulins and low degree of methylation (DM) pectin prevented binding to gut epithelial Caco2-cells, but effects were dependent on the molecules' chemistry, pathogen strain and growth phase. Pre-exposure to 3-fucosyllactose increased E. coli WA321 adhesion (28%, p < 0.05), and DM69 pectin increased E. coli ET8 (15 fold, p < 0.05) and E. coli WA321 (50%, p < 0.05) adhesion. Transcriptomics analysis revealed that DM69 pectin upregulated flagella and cell membrane associated genes. However, the top 10 downregulated genes were associated with lowering of bacteria virulence. DM69 pectin increased pathogen adhesion but bacterial virulence was attenuated illustrating different mechanisms may lower pathogen adhesion. Our study illustrates that both hMOs and NDCs can reduce adhesion or attenuate virulence of pathogens but that these effects are chemistry dependent.